Helminths from Sigmodontinae rodents (Muroidea : Cricetidae) in humid Chaco ecoregion (Argentina) : a list of species, host and geographical distribution - Gómez Muñóz, María de los Ángeles (2020)
Fil: Gómez Muñóz, María de los Ángeles. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.